CEO Network Centrality and the Likelihood of Financial Reporting Fraud. (16th March 2021) - Chahine, Salim; Fang, Yiwei; Hasan, Iftekhar; Mazboudi, Mohamad
Abstract : This paper investigates the association between CEO's relative position in the social network and the likelihood of being involved in corporate fraud. Tracing a large sample of US publicly listed firms, we find that CEO network centrality is inversely related to the likelihood of fraudulent financial reporting. We also document a significant spillover effect of financial reporting behaviour from the dominant (most central) CEO to other CEOs in the same social network, suggesting that the ethical corporate behaviour of CEOs is, on average, influenced by that of their dominant CEO in the network. We further find that the role of CEO network centrality in reducing fraud risk is more prominent in firms with lower auditor quality. Overall, our results suggest that network centrality is an important CEO trait that promotes ethical financial reporting behaviour within social networks.